Toward a Non-Androcentric Historical Analysis of Women's Prisons: The Cases of Santa Fe and Buenos Aires (Argentina, 1924-1936) - Calandria, Sol (2021)
This article analyzes the administration of women's prisons in Argentina during the process of state consolidation, using two prison cases: the Correctional Institution for Women (Santa Fe) and the Olmos Prison for Women (Buenos Aires). In both cases, the Sisters of the Good Shepherd's administration faced resistance from several state and non-state agents. We revisit an old issue using a new gender approach to investigate the relationship between female punishment, civil society, the state, its agents. The aim is to contribute toward a historical, non-androcentric analysis of women's prisons using archival research.